Professional Training of Electronics Engineers in the USA: Organization and Network of Higher Education Institutions - Pavlenko, Olha (Pedagogical Discourse, 2019)
US higher engineering education is attracting more and more students these years. While the effectiveness of US higher engineering education is generally recognized, few studies have focused on the organization of higher education within a specific engineering specialism. In this article, the current situation of US higher engineering education is reviewed focusing especially on programs for electronics professionals. The article studies the organization of higher education institutions (HEI) in the USA and outlines the features of a network of HEIs that provide Bachelor’s and Master’s programs in electronics. This paper describes the approaches to classification of US HEIs, presents quantitative data on the number of students depending on the type of HEI, and identifies three most popular types of US HEIs that attract the highest number of students by offering degrees in electronics. Three most respected world ranking systems of HEIs were compared in order to determine quantitative and territorial characteristics of HEIs in the field of electrical and electronic engineering and identify the types of leading HEIs that provide training for potential professionals in the field of electronics. The findings reveal that structural characteristics of HEIs granting degrees in electronics appear to be heterogeneous. The results also showed that electronics education programs are mostly delivered by such institutions as colleges and schools, and the most common educational program covers the full regulatory period. It is found that among the surveyed US HEIs offering training for electronics professionals half of the institutions are state-owned, and the distinguishing feature of the vast majority of universities is their focus on high quality of research and development.